Optically controlled reversible protein hydrogels based on photoswitchable fluorescent protein Dronpa. Issue 100 (4th December 2017) - Lyu, Shanshan; Fang, Jing; Duan, Tianyu; Fu, Linglan; Liu, Junqiu; Li, Hongbin
Abstract : Exploiting the optically controlled association and dissociation behavior of a photoswitchable fluorescent protein, Dronpa145N, here we demonstrate the engineering of an optically switchable reversible protein hydrogel using Dronpa145N-based protein building blocks. Abstract : Exploiting the optically controlled association and dissociation behavior of a photoswitchable fluorescent protein, Dronpa145N, here we demonstrate the engineering of an optically switchable reversible protein hydrogel using Dronpa145N-based protein building blocks. Our results open the possibility to optically tune the mechanical, chemical and structural properties of protein hydrogels.